(untitled) (Quinto Sol, 2023)
After the subjugation operated by the military campaigns of 1878-1885, the native population of northern Patagonia suffered forced relocation, the breakdown of socio-political and family units, the erasure of the identity of hundreds of minors and the declamation of the extinction of the indigenous cultural and social world. From this genocidal process, the agency of indigenous individuals and collectives was conditioned within the framework of the construction of a new society that was defined as “without Indians”. From then on, this became a condition for their possibilities of accessing land, as well as a principle of stigmatization and social differentiation. Our focus in this article is to address a particular instance of the agency of this population: the National Association of Aborigines. This organization stood out for its self-recognition as aboriginal and for its supra-community, trans-territorial and national structure. The ANA was active in a key period defining a political strategy that defended the indigenous producer, encouraged processes of communalization and articulation of the agency of the original peoples with other political actors, both in northern Patagonia and in the national context.